Positive electrode pre-lithiation material and preparation method thereof, positive electrode plate and lithium ion battery
By heating the mixture of lithium powder and sulfamate, a positive electrode prelithiated material with high specific capacity and stability is generated, which solves the problems of low specific capacity and poor stability of the positive electrode prelithiated material in the prior art, and improves the energy density and circulation performance of the lithium-ion battery.
Patent Information
- Application Number
- CN202510008259.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-02
AI Technical Summary
In the prior art, the specific capacity of the cathode prelithiated material has poor stability, resulting in low energy density and poor circulation performance of lithium-ion batteries.
By heating the mixture of lithium powder and sulfamate, a positive electrode prelithiated material including metal element, Li2O and Li2S was generated. This method uses reverse reaction to improve the specific capacity and stability of the material, and is compatible with the existing positive electrode sheet production process.
The specific capacity and stability of the positive electrode prelithiated material are improved, the energy density and cycling performance of the lithium-ion battery are enhanced, and the consumption of Li+ in the positive electrode sheet and the negative electrode is reduced.
Smart Images

Figure CN119833789A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery preparation, and in particular to a positive electrode pre-lithiation material and a preparation method thereof, a positive electrode plate and a lithium ion battery. Background Art
[0002] Lithium-ion batteries are widely used in the fields of 3C electronic products and large-scale electric and energy storage. Customers' demand for high-energy-density lithium-ion batteries is also increasing. Improving the energy density of lithium-ion batteries has become a common goal of researchers in this industry. However, during the first charging of lithium-ion batteries, the electrolyte will be reduced and decomposed on the surface of negative electrodes such as graphite to form a solid electrolyte interface film (SEI). The formation of the SEI film permanently consumes a large amount of active lithium from the positive electrode, causing irreversible capacity loss, which leads to a low initial coulomb efficiency (ICE) of lithium-ion batteries, thereby reducing the capacity and energy density of lithium-ion batteries. At the same time, as the charge and discharge cycle proceeds, the side reactions on the electrode surface increase, the active lithium decreases, and the cycle performance deteriorates. In order to solve the above problems, some researchers have proposed a pre-lithiation technology, which refers to adding lithium to the inside of the battery to supplement lithium ions before the lithium-ion battery works. The use of the above-mentioned pre-lithiation technology to supplement lithium to the electrode material can offset part of the irreversible lithium loss caused by the formation of the SEI film, thereby improving the total capacity, energy density and cycle performance of the battery.
[0003] The existing lithium replenishment methods mainly include positive electrode lithium replenishment and negative electrode lithium replenishment. Negative electrode lithium replenishment mainly uses metal lithium sheets, metal lithium powder or lithium-containing compounds (such as Li-Si alloy, Li 2.6 Co 0.4 N and other additives) for lithium compensation. Although these methods have good lithium replenishment effects, these lithium replenishment materials are highly active, have poor environmental stability, are incompatible with the existing preparation process of negative electrode plates, and have relatively high requirements for production process conditions. Compared with negative electrode lithium replenishment, positive electrode lithium replenishment is simpler to operate and has lower costs. Positive electrode lithium replenishment is to add additional lithium source during the positive electrode slurry process. During the battery charging process, the lithium source can release a large amount of active lithium and embed into the negative electrode to make up for the irreversible active lithium loss caused by the growth of negative electrode SEI. Positive electrode lithium replenishment has the most industrial application prospects due to its high safety and good compatibility with existing lithium-ion battery production processes.
[0004] At present, the existing positive electrode lithium replenishment mainly uses lithium-rich materials for lithium replenishment, such as Li2NiO2, Li6CoO4 and other lithium-rich compounds, but the specific capacity of such materials is relatively low. Another type of replenishment material, such as lithium salts such as Li2C4O4, LiC2O2, Li2C3O5 and Li2C4O6, although its specific capacity is high, will decompose and produce gas during the first charging process, which will reduce the safety performance of lithium-ion batteries.
[0005] In summary, researching and developing a positive electrode pre-lithiation material with high specific capacity and good stability is of great significance to improving the energy density and cycle performance of lithium-ion batteries. Summary of the invention
[0006] The main purpose of the present invention is to provide a positive electrode pre-lithiation material and a preparation method thereof, a positive electrode plate and a lithium ion battery, so as to solve the problems in the prior art of low specific capacity and poor stability of the positive electrode pre-lithiation material and low energy density and poor cycle performance of the lithium ion battery prepared therefrom.
[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a method for preparing a positive electrode pre-lithiation material, which comprises: heating a mixture of lithium powder and aminosulfonate to obtain a positive electrode pre-lithiation material, wherein the positive electrode pre-lithiation material comprises a metal element, Li2O and Li2S; wherein the aminosulfonate decomposes during the heating treatment; the metal element in the aminosulfonate and the metal element in the metal element are both Me, and Me is selected from one or more elements in Group VIIB and Group VIII.
[0008] The present application heats a mixture of lithium powder and aminosulfonate containing the Me element, wherein the lithium powder contains ≥99wt% of a lithium element and the remainder is lithium carbonate. When the lithium powder is heated, the lithium powder melts, and the aminosulfonate decomposes into metal oxides and metal sulfides. The generated metal oxides and metal sulfides can undergo a reverse chemical reaction with the lithium element and generate a metal element (Me element), Li2O and Li2S in situ, thereby obtaining a positive electrode pre-lithiation material.
[0009] The positive electrode pre-lithiation material in this application is obtained based on the reverse reaction, and has a high specific capacity, excellent stability and electrolyte compatibility, and is also compatible with the existing positive electrode production process. The positive electrode sheet containing the positive electrode pre-lithiation material is applied to a lithium-ion battery. During the charging process of the lithium-ion battery, the positive electrode pre-lithiation material can release a large amount of Li + , which can make up for the Li consumed during the first charging process + , thereby reducing the positive electrode active material in the positive electrode sheet and the Li +consumption, thereby improving the energy density and cycle performance of lithium-ion batteries.
[0010] Compared with other types, the use of the above-mentioned specific type of Me element in the present application is conducive to the occurrence of the reverse chemical reaction, making it easier to obtain a positive electrode pre-lithiation material containing Me, Li2O and Li2S, thereby playing its role in lithium replenishment, thereby improving the specific capacity and stability of the positive electrode pre-lithiation material.
[0011] Further, Me is selected from one or more of Ni, Co, Fe and Mn; preferably, Me is Ni and / or Co.
[0012] Compared with other types, the use of the above-mentioned types of Me elements is beneficial to further improve the specific capacity and stability of the positive electrode pre-lithiation material.
[0013] Furthermore, the molar ratio of the Li element in the lithium powder to the Me element in the aminosulfonate is (10-15):1.
[0014] Compared with other ranges, limiting the molar ratio of Li element in lithium powder to Me element in aminosulfonate within the above range is beneficial to improving the efficiency of the reverse conversion reaction, thereby helping to improve the stability and lithium replenishment effect of the prepared positive electrode pre-lithiation material, and is also beneficial to improving the utilization rate of raw materials and reducing production costs.
[0015] Furthermore, the D50 of the lithium powder is 0.1 to 10 μm.
[0016] Compared with other ranges, limiting the D50 of lithium powder within the above range is beneficial to improving the melting efficiency of lithium powder after heating, thereby further improving the efficiency of the reverse chemical reaction.
[0017] Furthermore, the D50 of a metal single substance is 20 to 200 nm, the D50 of Li2O is 50 to 500 nm, and the D50 of Li2S is 50 to 500 nm.
[0018] Compared with other ranges, limiting the D50 of metal elements, Li2O and Li2S within the above range is conducive to forming a uniformly mixed positive electrode pre-lithiation material, thereby facilitating the release of more Li during the charging process of the lithium-ion battery. + , to make up for the Li consumed during the first charging process + , which is beneficial to improve the energy density and cycle performance of lithium-ion batteries.
[0019] Furthermore, the heating treatment process is a laser beam irradiation process, preferably carried out using a laser; preferably, the laser is a semiconductor laser; preferably, a galvanometer is used to adjust the light output angle of the laser beam so that the light rays in the laser beam are parallel to each other; more preferably, the power of the laser is 300-360W; more preferably, the longitudinal movement rate of the laser beam is 500-1000mm / s, the lateral movement rate is 10-80mm / s, and the spot diameter is ≥0.5mm; more preferably, the laser beam irradiation process is carried out in a protective gas atmosphere; further preferably, the protective gas is selected from one or more of the group consisting of helium, argon, a mixture of xenon and radon, neon and krypton.
[0020] Compared with other methods, the above-mentioned method for heating treatment is beneficial to improving the efficiency of heating treatment, improving the efficiency of reverse conversion reaction, and at the same time, it is also beneficial to improve the purity of positive electrode pre-lithiation material and reduce impurity content, thereby improving the specific capacity and stability of positive electrode pre-lithiation material.
[0021] Furthermore, the laser beam irradiation process is a multi-stage intermittent treatment process; preferably, in the multi-stage intermittent treatment, the time of each laser beam irradiation process is 1 to 15 minutes, and the time interval between two adjacent laser beam irradiation processes is 0.5 to 5 minutes; more preferably, the mixture is stirred during the interval; further preferably, the stirring rate is 50 to 300 rpm.
[0022] Compared with continuous laser beam irradiation, the use of multi-stage intermittent treatment and limiting the process parameters of the laser beam irradiation process within the above-mentioned range is beneficial to controlling the temperature during the heating process and suppressing the occurrence of side reactions caused by local overheating, thereby improving the efficiency of the heating treatment and further improving the efficiency of the reverse transformation reaction.
[0023] Furthermore, the method for preparing the positive electrode pre-lithiation material further includes: mixing lithium powder with aminosulfonate to obtain a mixture; preferably, grinding is performed during the mixing process.
[0024] Compared with other methods, the above method is beneficial to improving the dispersibility of lithium powder and aminosulfonate, thereby improving the melting efficiency of lithium powder and the decomposition efficiency of aminosulfonate, and further improving the efficiency of the reverse reaction, which is beneficial to obtaining positive electrode pre-lithiation material.
[0025] In order to achieve the above-mentioned purpose, the second aspect of the present application further provides a positive electrode pre-lithiation material, which is prepared by the preparation method of the positive electrode pre-lithiation material provided in the present application.
[0026] The positive electrode pre-lithiation material in this application includes Me, Li2O and Li2S, which have high specific capacity, excellent stability and electrolyte compatibility, and are also compatible with the existing positive electrode production process. The positive electrode sheet containing the above positive electrode pre-lithiation material is used in a lithium-ion battery. During the charging process of the lithium-ion battery, the positive electrode pre-lithiation material can release a large amount of Li + , which can make up for the Li consumed during the first charging process + , thereby reducing the positive electrode active material in the positive electrode sheet and the Li + consumption, thereby improving the energy density and cycle performance of lithium-ion batteries.
[0027] In order to achieve the above-mentioned purpose, the third aspect of the present application further provides a positive electrode plate, including a positive electrode active material, a binder and a conductive agent, wherein the positive electrode active material includes a positive electrode material and the above-mentioned positive electrode pre-lithiation material provided in the present application.
[0028] The positive electrode material and the positive electrode pre-lithiation material provided in the present application are used as the positive electrode active material of the positive electrode plate in a lithium-ion battery. During the charging process of the lithium-ion battery, the positive electrode pre-lithiation material can release a large amount of Li + , which can make up for the Li consumed during the first charging process + , thereby reducing the positive electrode active material in the positive electrode sheet and the Li + consumption, thereby improving the energy density and cycle performance of lithium-ion batteries.
[0029] Furthermore, the positive electrode material is a ternary positive electrode material, and its general formula is LiNi x Co y Mn (1-x-y) O2, wherein 0.5≤x<1.0, 0<y≤0.2; preferably, the D50 of the positive electrode material is 2.5~12μm.
[0030] Compared with other types, using the above-mentioned type of ternary positive electrode material and limiting its D50 within the above-mentioned range is beneficial to improving the electrochemical properties such as energy density and cycle performance of lithium-ion batteries.
[0031] Furthermore, the weight ratio of the positive electrode pre-lithiation material to the positive electrode material is (1-10):100.
[0032] Compared with other ranges, limiting the weight ratio of the positive electrode pre-lithiation material to the positive electrode material within the above range is conducive to allowing the positive electrode pre-lithiation material to release more Li during the charging process of the lithium-ion battery. + , to make up for the Li consumed during the first charging process + , thereby further improving the energy density and cycle stability of lithium-ion batteries.
[0033] Furthermore, the weight ratio of the positive electrode active material, the binder and the conductive agent is (80-95):(2.5-10):(2.5-10).
[0034] Compared with other ranges, limiting the weight ratio of the positive electrode active material, the binder and the conductive agent within the above range is beneficial to exerting the electrochemical properties of the positive electrode material and improving the conductivity of the prepared positive electrode sheet.
[0035] Furthermore, the binder is selected from one or more of the group consisting of polyvinylidene fluoride, polytetrafluoroethylene and polypropylene.
[0036] Compared with other types, the use of the above-mentioned types of binders is beneficial to improving the stability of the prepared positive electrode plates.
[0037] Further, the conductive agent is selected from one or more of the group consisting of superconductive carbon black, conductive graphite, carbon nanotubes, graphene and carbon fiber.
[0038] Compared with other types, the use of the above-mentioned types of conductive agents is beneficial to improving the conductivity of electrons, thereby improving the electrochemical performance of lithium-ion batteries.
[0039] Furthermore, the compaction density of the positive electrode sheet is 2.9 to 3.5 g / cm 3 .
[0040] Compared with other ranges, limiting the compaction density of the positive electrode sheet within the above range is beneficial to improving the electrochemical capacity and cycle stability of the lithium-ion battery.
[0041] In order to achieve the above-mentioned purpose, the fourth aspect of the present application also provides a lithium-ion battery, including a positive electrode, a negative electrode, an electrolyte and a separator arranged between the positive electrode and the negative electrode; wherein the positive electrode includes the above-mentioned positive electrode plate provided in the present application.
[0042] The positive electrode sheet and positive electrode material provided in the present application are used as the positive electrode active material of the positive electrode sheet in a lithium-ion battery. During the charging process of the lithium-ion battery, the positive electrode pre-lithiation material in the positive electrode sheet can release a large amount of Li + , to make up for the Li consumed during the first charging process + , thereby reducing the positive electrode active material in the positive electrode sheet and the Li + consumption, thereby improving the energy density and cycle performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0044] Figure 1 The rate-cycle curves of the CR2016 button cells prepared in Example 1 and Comparative Example 1 of the present application are shown. DETAILED DESCRIPTION
[0045] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0046] As described in the background technology, the existing positive electrode pre-lithiation materials have the problems of low specific capacity and poor stability, which leads to low energy density and poor cycle performance of lithium-ion batteries made therefrom. In order to solve the above technical problems, the first aspect of the present application provides a method for preparing a positive electrode pre-lithiation material, the preparation method comprising: heating a mixture of lithium powder and aminosulfonate to obtain a positive electrode pre-lithiation material, the positive electrode pre-lithiation material comprising a metal element, Li2O and Li2S; wherein the aminosulfonate decomposes during the heating process; the metal element in the aminosulfonate and the metal element in the metal element are both Me, and Me is selected from one or more elements in Group VIIB and Group VIII.
[0047] The present application heats a mixture of lithium powder and aminosulfonate containing the Me element, wherein the lithium powder contains ≥99wt% of a lithium element and the remainder is lithium carbonate. When the lithium powder is heated, the lithium powder melts, and the aminosulfonate decomposes into metal oxides and metal sulfides. The generated metal oxides and metal sulfides can undergo a reverse chemical reaction with the lithium element and generate a metal element (Me element), Li2O and Li2S in situ, thereby obtaining a positive electrode pre-lithiation material.
[0048] The positive electrode pre-lithiation material in this application is obtained based on the reverse reaction, including Me, Li2O and Li2S, which has a high specific capacity, excellent stability and electrolyte compatibility, and is also compatible with the existing positive electrode production process. The positive electrode sheet containing the above positive electrode pre-lithiation material is used in a lithium-ion battery. During the charging process of the lithium-ion battery, the positive electrode pre-lithiation material can release a large amount of Li + , which can make up for the Li consumed during the first charging process + , thereby reducing the positive electrode active material in the positive electrode sheet and the Li + consumption, thereby improving the energy density and cycle performance of lithium-ion batteries.
[0049] Compared with other types, the use of a specific type of Me element in the present application is conducive to the occurrence of the reverse chemical reaction, making it easier to obtain a positive electrode pre-lithiation material with a higher specific capacity, thereby playing its role in lithium replenishment, and further improving the specific capacity and stability of the positive electrode pre-lithiation material.
[0050] In order to further improve the specific capacity and stability of the prepared positive electrode pre-lithiation material, thereby further exerting its lithium replenishment effect, preferably, Me includes but is not limited to one or more of Ni, Co, Fe and Mn.
[0051] In order to further improve the specific capacity and stability of the prepared positive electrode pre-lithiation material, thereby further exerting its lithium replenishment effect, more preferably, Me includes but is not limited to Ni and / or Co.
[0052] In a preferred embodiment, the molar ratio of the Li element in the lithium powder to the Me element in the aminosulfonate is (10-15): 1. The molar ratio of the Li element in the lithium powder to the Me element in the aminosulfonate includes but is not limited to the above range, and limiting it within the above range is conducive to improving the efficiency of the reverse conversion reaction, thereby facilitating the improvement of the stability and lithium replenishment effect of the prepared positive electrode pre-lithiation material, and is also conducive to improving the utilization rate of raw materials and reducing production costs.
[0053] In order to improve the melting efficiency of the lithium powder after being heated, thereby further improving the efficiency of the reverse conversion reaction, preferably, the D50 of the lithium powder is 0.1 to 10 μm.
[0054] In a preferred embodiment, the D50 of the metal element is 20-200nm, the D50 of Li2O is 50-500nm, and the D50 of Li2S is 50-500nm. The D50 of the metal element, Li2O and Li2S includes but is not limited to the above range. Limiting them to the above range is conducive to forming a uniformly mixed positive electrode pre-lithiation material, which is conducive to improving the specific capacity and stability of the positive electrode pre-lithiation material, thereby facilitating the release of more Li during the charging process of the lithium-ion battery. + , to make up for the Li consumed during the first charging process + , which is beneficial to reduce the positive electrode active material in the positive electrode sheet and the Li + consumption, which is beneficial to improve the energy density and cycle performance of lithium-ion batteries.
[0055] In the process of the laser emitting a laser beam, electrons will jump and fall back, and this process is accompanied by the conversion and release of energy, thereby releasing a large amount of heat in an instant. In a preferred embodiment, the process of heat treatment is a laser beam irradiation process, preferably performed by a laser. Compared with other methods, the use of the above method for heat treatment is conducive to improving the efficiency of the heat treatment, thereby helping to improve the efficiency of the reverse conversion reaction, and facilitating the acquisition of positive electrode pre-lithiation materials; it is also conducive to improving the safety of the heat treatment.
[0056] In order to further improve the energy utilization of the laser beam, further improve the efficiency of the laser beam irradiation process, and thus further improve the efficiency of the reverse chemical reaction, preferably, the laser is a semiconductor laser, and a galvanometer is used to adjust the light output angle of the laser beam in the semiconductor laser so that the light rays in the laser beam are parallel to each other.
[0057] In order to further improve the efficiency of the laser beam irradiation process, thereby further improving the efficiency of the reverse transformation reaction, preferably, the power of the laser is 300-360W, the longitudinal movement rate of the laser beam is 500-1000mm / s, the lateral movement rate is 10-80mm / s, and the spot diameter is ≥0.5mm.
[0058] In a preferred embodiment, the laser beam irradiation process is carried out in a protective gas atmosphere. Carrying out the laser beam irradiation process in a protective gas atmosphere is beneficial to suppressing the side reaction of lithium powder with air during the melting process, thereby facilitating the improvement of the purity of the positive electrode pre-lithiation material, facilitating the reduction of the impurity content, and further facilitating the improvement of the specific capacity and stability of the positive electrode pre-lithiation material.
[0059] In order to further inhibit the side reaction of lithium powder with air during the melting process and further improve the purity of the positive electrode pre-lithiation material, preferably, the protective gas includes but is not limited to one or more of the group consisting of helium, argon, a mixture of xenon and radon, neon and krypton.
[0060] In order to carry out the laser beam irradiation process under a protective gas atmosphere, thereby further improving the processing efficiency and the purity of the positive electrode pre-lithiation material, it is more preferred to use a glove box laser integrated instrument for heating treatment, wherein the water content in the glove box is ≤0.01ppm and the oxygen content is ≤0.01ppm.
[0061] In a preferred embodiment, the laser beam irradiation process is a multi-stage intermittent treatment process. Compared with continuous laser beam irradiation, the multi-stage intermittent treatment is convenient for controlling the temperature during the heating process, which is beneficial to suppress the occurrence of side reactions caused by local overheating, thereby improving the efficiency of the heating treatment, and further improving the efficiency of the reverse transformation reaction.
[0062] In order to further control the temperature during the laser beam irradiation process within a more suitable range, thereby further suppressing the occurrence of side reactions caused by local overheating, and further improving the efficiency of the reverse transformation reaction, preferably, in the multi-stage intermittent treatment, the time of each laser beam irradiation process is 1 to 15 minutes, and the time interval between two adjacent laser beam irradiation processes is 0.5 to 5 minutes.
[0063] In a preferred embodiment, the mixture is stirred during the intervals. Stirring during the intervals of each treatment cycle is beneficial to making the mixture of lithium powder and aminosulfonate heated more evenly, and is beneficial to suppressing the occurrence of other side reactions caused by excessive local temperature, thereby improving the safety of the reaction; it is also beneficial to improving the dispersibility of lithium powder and aminosulfonate, and is beneficial to improving the melting efficiency of lithium powder and the decomposition efficiency of aminosulfonate, thereby improving the efficiency of the reverse reaction.
[0064] In order to make the mixture of lithium powder and aminosulfonate heated more evenly, and to further improve the dispersibility of lithium powder and aminosulfonate, further improve the melting efficiency of lithium powder and the decomposition efficiency of aminosulfonate, thereby further improving the efficiency of the reverse reaction, preferably, the stirring rate is 50-300rpm.
[0065] In a preferred embodiment, the preparation method of the positive electrode pre-lithiation material further includes: mixing lithium powder with aminosulfonate to obtain a mixture. Pre-mixing the lithium powder with the aminosulfonate and then heating it is beneficial to improve the dispersibility of the lithium powder and the aminosulfonate, thereby improving the melting efficiency of the lithium powder and the decomposition efficiency of the aminosulfonate, and further improving the efficiency of the reverse reaction, which is beneficial to obtaining the positive electrode pre-lithiation material.
[0066] In order to further improve the dispersibility of lithium powder and aminosulfonate, thereby further improving the melting efficiency of lithium powder and the decomposition efficiency of aminosulfonate, and further improving the efficiency of the reverse chemical reaction, preferably, grinding is performed during the mixing process.
[0067] The second aspect of the present application further provides a positive electrode pre-lithiation material, which is prepared by the preparation method of the positive electrode pre-lithiation material provided in the present application.
[0068] The positive electrode pre-lithiation material in this application includes Me, Li2O and Li2S, which have high specific capacity, excellent stability and electrolyte compatibility, and are also compatible with the existing positive electrode production process. The positive electrode sheet containing the above positive electrode pre-lithiation material is used in a lithium-ion battery. During the charging process of the lithium-ion battery, the positive electrode pre-lithiation material can release a large amount of Li + , which can make up for the Li consumed during the first charging process +, thereby reducing the positive electrode active material in the positive electrode sheet and the Li + consumption, thereby improving the energy density and cycle performance of lithium-ion batteries.
[0069] The third aspect of the present application also provides a positive electrode plate, which includes a positive electrode active material, a binder and a conductive agent, wherein the positive electrode active material includes a positive electrode material and the above-mentioned positive electrode pre-lithiation material provided in the present application.
[0070] The positive electrode active material in the positive electrode sheet provided by the present application includes a positive electrode material and the positive electrode pre-lithiation material provided by the present application. The positive electrode pre-lithiation material provided by the present application has a high specific capacity, excellent stability and electrolyte compatibility, and can also be well compatible with the existing positive electrode sheet production process. It and the positive electrode material are used as the positive electrode active material of the positive electrode sheet in a lithium-ion battery. During the charging process of the lithium-ion battery, the positive electrode pre-lithiation material can release a large amount of Li + , which can make up for the Li consumed during the first charging process + , thereby reducing the positive electrode active material in the positive electrode sheet and the Li + consumption, thereby improving the energy density and cycle performance of lithium-ion batteries.
[0071] In a preferred embodiment, the positive electrode material is a ternary positive electrode material, the general formula of which is LiNi x Co y Mn (1-x-y) O2, wherein 0.5≤x<1.0, 0<y≤0.2. Compared with other types of positive electrode materials, the use of the above-mentioned type of ternary positive electrode materials is beneficial to improving the electrochemical properties of lithium-ion batteries, such as energy density and cycle performance.
[0072] In order to make the positive electrode pre-lithiation material release more Li during the charging process of lithium-ion batteries + , to make up for the Li consumed during the first charging process + , thereby further improving the energy density and cycle stability of the lithium-ion battery. Preferably, the weight ratio of the positive electrode pre-lithiation material to the positive electrode material is (1-10):100.
[0073] In order to increase the specific surface area of the positive electrode material and to improve the mixing uniformity of the positive electrode material and the positive electrode pre-lithiation material, preferably, the D50 of the positive electrode material is 2.5 to 12 μm.
[0074] In a preferred embodiment, the weight ratio of the positive electrode active material, the binder and the conductive agent is (80-95): (2.5-10): (2.5-10). The weight ratio of the positive electrode active material, the binder and the conductive agent includes but is not limited to the above range. Limiting it within the above range is conducive to improving the conductivity of the prepared positive electrode sheet, and is conducive to exerting the electrochemical properties of the positive electrode material, thereby helping to improve the energy density and cycle performance of the lithium-ion battery.
[0075] In order to improve the stability of the layer formed by the positive electrode active material, thereby improving the stability of the positive electrode sheet, in a preferred embodiment, the binder includes but is not limited to one or more of the group consisting of polyvinylidene fluoride, polytetrafluoroethylene and polypropylene.
[0076] In a preferred embodiment, the conductive agent includes but is not limited to one or more of the group consisting of superconductive carbon black (Super P), conductive graphite, carbon nanotubes, graphene and carbon fiber. Compared with other types, the use of the above-mentioned conductive agents is conducive to improving the conductivity of electrons, thereby improving the charging and discharging efficiency of lithium-ion batteries, and further improving the electrochemical performance of lithium-ion batteries. The above-mentioned conductive graphite in the present application can be KS-6 (manufacturer: Swiss Temeco).
[0077] In a preferred embodiment, the compaction density of the positive electrode sheet is 2.9 to 3.5 g / cm 3 The compaction density of the positive electrode sheet includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the electrochemical capacity and cycle stability of the lithium-ion battery.
[0078] The fourth aspect of the present application also provides a method for preparing the above-mentioned positive electrode plate provided in the present application, and the preparation method comprises: step S1, mixing a positive electrode active material, a binder, a conductive agent and a solvent to obtain a positive electrode slurry, wherein the positive electrode active material comprises a positive electrode material and the above-mentioned positive electrode pre-lithiation material provided in the present application; step S2, coating the positive electrode slurry on the surface of the current collector to obtain a positive electrode slurry layer; step S3, sequentially drying and pressing the positive electrode slurry layer to obtain a positive electrode plate.
[0079] In the preparation method of the positive electrode sheet of the present application, a positive electrode slurry containing a positive electrode pre-lithiation material can be obtained through step S1, and it is coated on the surface of the current collector in step S2, and then dried and pressed (such as rolling and slicing) in step S3 in sequence to obtain a positive electrode sheet. The above-mentioned positive electrode pre-lithiation material provided in the present application has a high specific capacity, excellent stability and electrolyte compatibility, and can also be well compatible with the preparation method of the above-mentioned positive electrode sheet of the present application. It and the positive electrode material are used as the positive electrode active material of the positive electrode sheet in a lithium-ion battery. During the charging process of the lithium-ion battery, the above-mentioned positive electrode pre-lithiation material can release a large amount of Li+ , which can make up for the Li consumed during the first charging process + , thereby reducing the positive electrode active material in the positive electrode sheet and the Li + consumption, thereby improving the energy density and cycle performance of lithium-ion batteries.
[0080] The solvent used in the present application can be any commonly used solvent in the art. In a preferred embodiment, the solvent includes but is not limited to one or more of the group consisting of N-methylpyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, tetramethylurea and trimethyl phosphate.
[0081] In a preferred embodiment, the solid content of the positive electrode slurry is 30-50 wt %. The solid content of the positive electrode slurry includes but is not limited to the above range, and limiting it within the above range facilitates subsequent coating on the surface of the current collector.
[0082] In order to improve the coating uniformity of the positive electrode slurry on the surface of the current collector and to improve the electrochemical capacity of the lithium ion battery, preferably, the coating thickness of the positive electrode slurry is 100 to 400 μm.
[0083] In a preferred embodiment, the coating amount per unit area of the positive electrode slurry is 70 to 150 g / cm 2 The coating amount per unit area of the positive electrode slurry includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the electrochemical capacity, energy density and cycle performance of the lithium-ion battery.
[0084] In order to improve the electrochemical performance of the lithium ion battery, in a preferred embodiment, the current collector is an aluminum foil, and preferably, the thickness of the aluminum foil is 6 to 20 μm.
[0085] In a preferred embodiment, the drying in step S3 is vacuum drying, preferably with a vacuum degree of ≤500 Pa. Compared with normal pressure drying, vacuum drying is beneficial to improving the drying efficiency and the removal rate of the solvent in the positive electrode slurry layer, thereby facilitating subsequent pressing and molding.
[0086] In order to further improve the removal rate of the solvent in the positive electrode slurry layer, preferably, the drying temperature is 80 to 120° C. and the drying time is 12 to 24 hours.
[0087] The fifth aspect of the present application also provides a lithium-ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator arranged between the positive electrode and the negative electrode, wherein the positive electrode comprises the above-mentioned positive electrode plate provided in the present application.
[0088] The positive electrode active material in the above-mentioned positive electrode sheet provided in the present application includes the above-mentioned positive electrode pre-lithiation material provided in the present application. The positive electrode pre-lithiation material in the present application has a high specific capacity, excellent stability and electrolyte compatibility, and can also be well compatible with the existing positive electrode sheet production process. It and the positive electrode material are used as the positive electrode active material of the positive electrode sheet in a lithium-ion battery. During the charging process of the lithium-ion battery, the positive electrode pre-lithiation material can release a large amount of Li + , which can make up for the Li consumed during the first charging process + , thereby reducing the positive electrode active material in the positive electrode sheet and the Li + consumption, thereby improving the energy density and cycle performance of lithium-ion batteries.
[0089] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0090] It should be noted that the positive electrode pre-lithiation materials in all the embodiments of the present application are prepared using a glove box laser integrated instrument (Wuhan Zhonggu Lianchuang Optoelectronics Technology Co., Ltd., ZG-1GY-500 / 700B), wherein the glove box is an argon atmosphere, the water content is ≤0.01ppm, and the oxygen content is ≤0.01ppm.
[0091] Example 1
[0092] A method for preparing a positive electrode sheet comprises the following steps:
[0093] (1) In a glove box, 2 g of cobalt sulfamate (CAS No.: 14017-41-5) and 0.6 g of lithium powder (D50: 5 μm, purity: 99.8 wt%) were weighed and placed in a mortar for grinding to obtain a mixture;
[0094] (2) The mixture was transferred into a quartz crucible, and the mixture was subjected to three-stage intermittent heating treatment using a semiconductor laser in a glove box, wherein the power of the semiconductor laser was 350 W, the longitudinal moving speed of the laser beam was 1000 mm / s, the lateral moving speed was 50 mm / s, and the spot diameter was 0.5 mm. The first stage of heating treatment was stopped after 10 min, and the second stage of heating treatment was started after stirring at a rate of 300 rpm for 1 min, the second stage of heating treatment was stopped after 5 min, and the third stage of heating treatment was started after stirring at a rate of 150 rpm for 1 min, the third stage of heating treatment was stopped after 3 min, and the reaction was terminated after stirring at a rate of 50 rpm for 1 min, to obtain a positive electrode pre-lithiation material including Co, Li2O and Li2S;
[0095] In the positive electrode pre-lithiation material prepared in step (2), the D50 of Co single substance is 50nm, the D50 of Li2O is 200nm, and the D50 of Li2S is 200nm;
[0096] (3) Weigh 0.1 g of the positive electrode pre-lithiation material prepared in step (2) and 4.9 g of the ternary positive electrode material LiNi 0.7 Co 0.1 Mn 0.2 O2 (the preparation method of the ternary positive electrode material can refer to patent CN111777104A), and the two are mixed evenly to obtain the positive electrode active material;
[0097] (4) The positive electrode active material, superconductive carbon black (SUPER PLI) and polyvinylidene fluoride (PVDF) were mixed with N-methylpyrrolidone (NMP) solution in a weight ratio of 90:5:5, and stirred at 25° C. for 2 h to obtain a positive electrode slurry with a solid content of 45 wt %;
[0098] (5) coating the positive electrode slurry on one side of a 20 μm thick aluminum foil to obtain a positive electrode slurry layer, wherein the coating thickness of the slurry is 400 μm;
[0099] (6) The positive electrode slurry layer was placed in a vacuum oven at 110°C and dried for 20 hours, and then rolled and sliced to obtain a positive electrode sheet. The compaction density of the positive electrode sheet was 3.5 g / cm 3 .
[0100] Example 2
[0101] The difference from Example 1 is that in step (1), 1.5 g of nickel sulfamate (CAS No.: 13770-89-3) and 1.0 g of lithium powder are weighed in a glove box and ground in a mortar to obtain a mixture. The remaining steps are the same as in Example 1.
[0102] The positive electrode pre-lithiation material prepared in Example 2 includes Ni single substance, Li2O and Li2S, wherein the D50 of Ni single substance is 100nm, the D50 of Li2O is 200nm, and the D50 of Li2S is 200nm.
[0103] Example 3
[0104] The difference from Example 1 is that in step (1), 3.3 g of aminosulfonate cobalt, 1.5 g of aminosulfonate nickel and 2 g of lithium powder are weighed in a glove box and ground in a mortar to obtain a mixture, and the remaining steps are the same as in Example 1.
[0105] The positive electrode pre-lithiation material prepared in Example 3 includes Co single substance, Ni single substance, Li2O and Li2S, wherein the D50 of Co single substance is 50nm, the D50 of Ni single substance is 100nm, the D50 of Li2O is 200nm, and the D50 of Li2S is 200nm.
[0106] Example 4
[0107] The difference from Example 1 is that in step (1), an equimolar amount of ferrous sulfamate (CAS No.: 14017-39-1) is used to replace cobalt sulfamate, and the remaining steps are the same as those in Example 1.
[0108] The positive electrode pre-lithiation material prepared in Example 4 includes Fe, Li2O and Li2S, wherein the D50 of Fe is 20nm, the D50 of Li2O is 50nm, and the D50 of Li2S is 50nm.
[0109] Example 5
[0110] The difference from Example 1 is that the molar ratio of the Co element in the aminosulfonate cobalt to the Li element in the lithium powder in step (1) is 1:10, and the remaining steps are the same as Example 1.
[0111] Example 6
[0112] The difference from Example 1 is that the molar ratio of the Co element in the aminosulfonate cobalt to the Li element in the lithium powder in step (1) is 1:15, and the remaining steps are the same as those in Example 1.
[0113] Example 7
[0114] The difference from Example 1 is that the molar ratio of the Co element in the aminosulfonate cobalt to the Li element in the lithium powder in step (1) is 1:20, and the remaining steps are the same as Example 1.
[0115] Example 8
[0116] The difference from Example 1 is that in step (2), the mixture is subjected to two-stage intermittent heating treatment using a semiconductor laser in a glove box, wherein the power of the semiconductor laser is 300 W, the longitudinal moving speed of the laser beam is 500 mm / s, the lateral moving speed is 10 mm / s, the spot diameter is 0.8 mm, the heating is stopped after the first heating treatment is carried out for 15 min, and the second heating treatment is started after stirring at a rate of 200 rpm for 1 min, the heating is stopped after the second heating treatment is carried out for 5 min, and the reaction is terminated after stirring at a rate of 100 rpm for 1 min, and the remaining steps are the same as Example 1.
[0117] Example 9
[0118] The difference from Example 1 is that in step (2), the mixture is irradiated with a continuous laser beam using a semiconductor laser in a glove box, the irradiation is stopped after 18 minutes, and the reaction is terminated after stirring at a rate of 300 rpm for 1 minute. The remaining steps are the same as in Example 1.
[0119] Example 10
[0120] The difference from Example 1 is that in step (2), the power of the semiconductor laser is 250 W, the longitudinal moving speed of the laser beam is 300 mm / s, the lateral moving speed is 5 mm / s, the spot diameter is 0.4 mm, and the remaining steps are the same as Example 1.
[0121] Embodiment 11
[0122] The difference from Example 1 is that in step (3), 0.25 g of the positive electrode pre-lithiation material prepared in step (2) and 4.75 g of the ternary positive electrode material LiNi 0.7 Co 0.1 Mn 0.2 After the O2 is evenly mixed, the positive electrode active material is obtained, and the remaining steps are the same as those in Example 1.
[0123] Example 12
[0124] The difference from Example 1 is that in step (3), 0.45 g of the positive electrode pre-lithiation material prepared in step (2) and 4.55 g of the ternary positive electrode material LiNi 0.7 Co 0.1 Mn 0.2 After the O2 is evenly mixed, the positive electrode active material is obtained, and the remaining steps are the same as those in Example 1.
[0125] Embodiment 13
[0126] The difference from Example 1 is that in step (3), 1 g of the positive electrode pre-lithiation material prepared in step (2) and 4 g of the ternary positive electrode material LiNi 0.7 Co 0.1 Mn 0.2 After the O2 is evenly mixed, the positive electrode active material is obtained, and the remaining steps are the same as those in Example 1.
[0127] Comparative Example 1
[0128] The difference from Example 1 is that steps (1) and (2) are omitted, and in step (3), 5 g of ternary positive electrode material LiNi 0.7 Co 0.1 Mn 0.2 O2 is used as the positive electrode active material, that is, no positive electrode pre-lithiation material is added to the positive electrode active material, and the remaining steps are the same as those in Example 1.
[0129] Comparative Example 2
[0130] The difference from Example 1 is that steps (1) and (2) are omitted, an equal amount of Co / Li2O is used to replace the positive electrode pre-lithiation material in step (3), and the remaining steps are the same as those in Example 1.
[0131] Comparative Example 3
[0132] The difference from Example 1 is that steps (1) and (2) are omitted, an equal amount of Co / Li2S is used to replace the positive electrode pre-lithiation material in step (3), and the remaining steps are the same as Example 1.
[0133] The positive electrode sheets prepared in the above-mentioned Examples 1 to 13 and Comparative Examples 1 to 3 of the present application were used as the positive electrode, the metal lithium sheet was used as the negative electrode, 1.0 mol / L LiPF6 / EC+DEC+EMC was used as the electrolyte, and the diaphragm prepared by the wet process was used as the diaphragm to assemble CR2016 button batteries. After standing for 4 hours, the electrochemical properties of the batteries were tested.
[0134] The following performance tests were performed on the CR2016 button batteries prepared in all the embodiments and comparative examples of the present application:
[0135] (1) The test conditions for the first charge specific capacity and the first coulombic efficiency are as follows: constant current charging at a rate of 0.2C, with a voltage range of 2.8 to 4.5V;
[0136] (2) The test conditions for the first discharge specific capacity and the 0.2C return specific capacity are as follows: constant current discharge at a 0.2C rate, with a voltage range of 2.8 to 4.5 V;
[0137] (3) The test conditions for 1C discharge specific capacity are as follows: constant current discharge at 1C rate, voltage range 2.8~4.5V;
[0138] (4) The test conditions for capacity retention are as follows: 1C rate, 25°C, voltage range 2.8-4.5V, and 50 cycles.
[0139] The test results are shown in Table 1. The rate-cycle curves of the CR2016 button cells prepared in Example 1 and Comparative Example 1 are shown in Table 1. Figure 1 As shown by Figure 1 It can be seen that the CR2016 button cell prepared in Example 1 has better cycle performance.
[0140] Table 1
[0141]
[0142] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0143] Compared with the existing positive electrode materials, the above-mentioned positive electrode pre-lithiation material provided in the present application has higher mass energy density and volume energy density, which is more than 4 times that of the existing positive electrode materials, and has a larger charge and discharge voltage hysteresis. When the voltage reaches 3V during the charging process, Li + It can be almost completely discharged. This voltage is within the upper limit voltage range of the ternary positive electrode material, and the discharge voltage range is 1.2~0.01V. This voltage is lower than the lower limit voltage of the ternary positive electrode material. Therefore, the larger voltage hysteresis provides a large amount of Li + Used to make up for the Li consumed by the formation of SEI film + When it and the positive electrode material are used as the positive electrode active material of the positive electrode sheet in a lithium-ion battery, only 1 to 10 wt% of the above positive electrode pre-lithiation material needs to be added to offset the initial Li loss. At the same time, the mass energy density and volume energy density of the lithium-ion battery can be increased by 8 to 13% and 11 to 14% respectively.
[0144] Comparing Example 1 of the present application with Comparative Example 1, it can be seen that compared with Comparative Example 1, the first charging capacity (0.2C) of the CR2016 button cell prepared in Example 1 is increased by 9.6 mAh / g, the discharge capacity remains basically the same, and the capacity retention rate is increased by 9%. This shows that the positive electrode pre-lithiation material and the positive electrode material in the present application are applied as the positive electrode active material of the positive electrode sheet to the lithium ion battery. During the charging process of the lithium ion battery, the positive electrode pre-lithiation material can release a large amount of Li + , which can make up for the Li consumed during the first charging process + , thereby reducing the positive electrode active material in the positive electrode sheet and the Li + consumption, thereby improving the energy density and cycle performance of lithium-ion batteries.
[0145] Comparing Example 1 with Comparative Examples 2 and 3, it can be seen that compared with the positive electrode pre-lithiation material comprising only Co and Li2O or Co and Li2S, the positive electrode pre-lithiation material prepared in Example 1 comprises Co, Li2O and Li2S, and its first charge capacity and capacity retention rate are higher, which shows that the positive electrode pre-lithiation material of the present application has a higher specific capacity, good stability and electrolyte compatibility, and is applied to lithium-ion batteries. During the charging process of the lithium-ion battery, more Li + , to make up for the Li consumed during the first charging process + , thereby reducing the positive electrode active material in the positive electrode sheet and the Li + consumption, thereby improving the energy density and cycle performance of lithium-ion batteries.
[0146] By comparing Examples 1 to 4 and Comparative Examples 1 to 3, it can be seen that, compared with other types, the use of a specific type of Me element in the present application is conducive to the occurrence of the reverse chemical reaction, making it easier to obtain a positive electrode pre-lithiation material containing Me, Li2O and Li2S, thereby facilitating the lithium replenishment effect, and further facilitating the improvement of the energy density and cycle performance of lithium-ion batteries.
[0147] By comparing Examples 1, 5 to 7, it can be seen that, compared with other ranges, limiting the molar ratio of the Li element in the lithium powder to the Me element in the aminosulfonate within the above-mentioned range of the present application is beneficial to improving the efficiency of the reverse conversion reaction, thereby helping to improve the lithium replenishment effect of the prepared positive electrode pre-lithiation material, and further helping to improve the cycle performance of the lithium-ion battery.
[0148] By comparing Examples 1, 8 to 10, it can be seen that compared with continuous laser beam irradiation, the use of multi-stage intermittent treatment and limiting the process parameters of each stage of treatment within the above-mentioned range of the present application is beneficial to controlling the temperature during the heating process, suppressing the occurrence of side reactions caused by local overheating, and improving the efficiency of the heating treatment, thereby improving the efficiency of the reverse transformation reaction, and further improving the lithium replenishment effect of the prepared positive electrode pre-lithiation material.
[0149] Comparing Examples 1, 11 to 13, it can be seen that the weight ratio of the positive electrode pre-lithiation material to the ternary positive electrode material is not limited to the above range, and limiting it to the above range is conducive to allowing the positive electrode pre-lithiation material to release more Li during the charging process of the lithium-ion battery. + , to make up for the Li consumed during the first charging process + , which is beneficial to improve the cycle performance of lithium-ion batteries.
[0150] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0151] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a positive electrode pre-lithiation material, characterized in that: The preparation method of the positive electrode pre-lithiation material comprises: heating a mixture of lithium powder and aminosulfonate to obtain the positive electrode pre-lithiation material, wherein the positive electrode pre-lithiation material comprises a metal element, Li2O and Li2S; wherein the aminosulfonate decomposes during the heating process; the metal element in the aminosulfonate and the metal element in the metal element are both Me, and the Me is selected from one or more elements in Group VIIB and Group VIII.
2. The method for preparing the positive electrode pre-lithiation material according to claim 1, characterized in that: The molar ratio of the Li element in the lithium powder to the Me element in the aminosulfonate is (10-15):1; Preferably, the D50 of the lithium powder is 0.1 to 10 μm; Preferably, the Me is selected from one or more of Ni, Co, Fe and Mn; more preferably Ni and / or Co; Preferably, the D50 of the metal element is 20 to 200 nm, the D50 of the Li2O is 50 to 500 nm, and the D50 of the Li2S is 50 to 500 nm.
3. The method for preparing the positive electrode pre-lithiation material according to claim 1, characterized in that: The heating process is a laser beam irradiation process, preferably performed using a laser; Preferably, the laser is a semiconductor laser; Preferably, a galvanometer is used to adjust the light output angle of the laser beam so that the light rays in the laser beam are parallel to each other; Preferably, the power of the laser is 300-360W; Preferably, the longitudinal movement rate of the laser beam is 500-1000 mm / s, the lateral movement rate is 10-80 mm / s, and the spot diameter is ≥0.5 mm; Preferably, the laser beam irradiation process is carried out in a protective gas atmosphere; more preferably, the protective gas is one or more selected from the group consisting of helium, argon, a mixture of xenon and radon, neon and krypton.
4. The method for preparing the positive electrode pre-lithiation material according to claim 3, characterized in that: The laser beam irradiation process is a multi-stage intermittent processing process; Preferably, in the multi-stage intermittent treatment, the duration of each laser beam irradiation process is 1 to 15 minutes, and the interval between two adjacent laser beam irradiation processes is 0.5 to 5 minutes; More preferably, the mixture is stirred during the interval; further preferably, the stirring rate is 50-300 rpm.
5. The method for preparing a positive electrode pre-lithiation material according to any one of claims 1 to 4, characterized in that: The method for preparing the positive electrode pre-lithiation material further comprises: mixing the lithium powder with the aminosulfonate to obtain the mixture; Preferably, grinding is performed during the mixing process.
6. A positive electrode pre-lithiation material, characterized in that: The positive electrode pre-lithiation material is prepared by the method for preparing the positive electrode pre-lithiation material according to any one of claims 1 to 5.
7. A positive electrode sheet, characterized in that: The positive electrode plate comprises a positive electrode active material, a binder and a conductive agent, and the positive electrode active material comprises a positive electrode material and the positive electrode pre-lithiation material according to claim 6.
8. The positive electrode sheet according to claim 7, characterized in that: The positive electrode material is a ternary positive electrode material, and its general formula is LiNi x Co y Mn (1-x-y) O2, where 0.5≤x<1.0, 0<y≤0.2; Preferably, the weight ratio of the positive electrode pre-lithiation material to the positive electrode material is (1-10):100; Preferably, the D50 of the positive electrode material is 2.5-12 μm.
9. The positive electrode sheet according to claim 7 or 8, characterized in that: The weight ratio of the positive electrode active material, the binder and the conductive agent is (80-95):(2.5-10):(2.5-10); Preferably, the binder is selected from one or more of the group consisting of polyvinylidene fluoride, polytetrafluoroethylene and polypropylene; Preferably, the conductive agent is selected from one or more of the group consisting of superconductive carbon black, conductive graphite, carbon nanotubes, graphene and carbon fiber; Preferably, the compaction density of the positive electrode sheet is 2.9 to 3.5 g / cm 3 .
10. A lithium ion battery comprising a positive electrode, a negative electrode, an electrolyte and a separator arranged between the positive electrode and the negative electrode, characterized in that: The positive electrode comprises the positive electrode sheet according to any one of claims 7 to 9.
Citation Information
Patent Citations
Preparation method of positive electrode pre-lithiation material, product and application
CN112542589A
Positive electrode lithium supplementing material, preparation method and application thereof
CN115911610A
Positive electrode lithium supplement agent and preparation method and application thereof
CN116470048A
Pre-lithiation material of ternary positive electrode material of lithium ion battery and preparation method of pre-lithiation material
CN117936943A
Cited By
Method for efficiently extracting lithium from sulfonate compounded low-temperature reinforced roasted lepidolite and application
CN120664565A